The Application of Expiration in Sanctioning Procedures of the State Contracting Court in Peru (Justicia &Derecho, 2026)
This article examines expiration in Peruvian Administrative Sanctioning Proceedings to protect citizens’ rights to legalcertainty and predictability in State Contracting Court procedures. Using a qualitative-descriptive methodology, itanalyzes the regulatory framework evolution, jurisprudential developments, and interpretive scenarios regarding expiration application in public procurement sanctioning proceedings.
Keywords: Expiration; Sanctioning Administrative Procedure; LPAG; SPT